2013
DOI: 10.1002/cite.201300036
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Modeling of Phase Equilibria and Interfacial Properties Using the PCP‐SAFT Model

Abstract: Am Beispiel der Hydroformylierung von Olefinen wurde die Modellierung von temperaturgesteuerten Lösungsmittelsystemen untersucht. Dazu werden Informationen über Flüssig/flüssig-und Gas/flüssig-Gleichgewichte sowie Grenzflächeneigenschaften benötigt. Es konnte gezeigt werden, dass die Perturbed Chain Polar Statistical Associating Fluid Theory (PCP-SAFT) in Kombination mit der Dichtegradiententheorie ein geeignetes Modellierungswerkzeug hierfür ist. Die Beschreibung der unterschiedlichen thermodynamischen Eigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…14,15 In the work of van Schilt et al, 20 PC-SAFT 14,15 was used to predict the high-pressure phase behavior of poly(cyclohexene carbonate) and cyclohexane oxide and CO 2 , where a good agreement between experimental and modeling results could be shown. Schafer et al 21 combined the density gradient theory with PCP-SAFT 22 to model the interfacial properties in various vapor−liquid-and liquid−liquid-equilibria. Hassanpouryouzband et al 3 showed the prediction capability of PC-SAFT by investigating the solubility of heavy components in hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 In the work of van Schilt et al, 20 PC-SAFT 14,15 was used to predict the high-pressure phase behavior of poly(cyclohexene carbonate) and cyclohexane oxide and CO 2 , where a good agreement between experimental and modeling results could be shown. Schafer et al 21 combined the density gradient theory with PCP-SAFT 22 to model the interfacial properties in various vapor−liquid-and liquid−liquid-equilibria. Hassanpouryouzband et al 3 showed the prediction capability of PC-SAFT by investigating the solubility of heavy components in hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Tumakaka et al modeled various complex systems, containing associating and polar as well as nonpolar substances with PC-SAFT. , In the work of van Schilt et al, PC-SAFT , was used to predict the high-pressure phase behavior of poly­(cyclohexene carbonate) and cyclohexane oxide and CO 2 , where a good agreement between experimental and modeling results could be shown. Schäfer et al . combined the density gradient theory with PCP-SAFT to model the interfacial properties in various vapor–liquid- and liquid–liquid-equilibria.…”
Section: Introductionmentioning
confidence: 99%
“…This approach requires an excellent description of the LLE and the interfacial tension of systems hydrocarbon + water for hydrocarbons having different carbon numbers. PC-SAFT could already be successfully used within the DGT framework for a large variety of systems. The agreement of the calculated interfacial tension with the experimental data strongly depends on the agreement of the calculated LLE with the experimental data. The challenges related to the correct modeling of these LLEs were discussed in great detail by Haarmann et al Using a temperature-dependent binary interaction parameter allowed them to correctly describe the mutual solubilities of hydrocarbons and water including the aqueous-solubility minima for hydrocarbons ranging from n -pentane to n -undecane.…”
Section: Introductionmentioning
confidence: 99%